Hospice and palliative care utilization in 16 004 232 medicare claims: comparing trauma to surgical and medical inpatients - Matthew M Carrick; Samir M Fakhry; Yan Shen; Ransom J Wyse; Jeneva M Garland; Dorraine D Watts; Melissa Red Hoffman (Trauma Surgery & Acute Care Open)
Background Hospice and palliative care (PC) utilization is increasing in geriatric inpatients, but limited research exists comparing rates among trauma, surgical and medical specialties. The goal of this study was to determine whether there are differences among these three groups in rates of hospice and PC utilization.Methods Patients from Centers for Medicare & Medicaid Services (CMS) Inpatient Standard Analytical Files for 2016–2020 aged ≥65 years were analyzed. Patients with a National Trauma Data Standard-qualifying ICD-10 injury code with abbreviated injury score ≥2 were classified as ‘trauma’; the rest as ‘surgical’ or ‘medical’ using CMS MS-DRG definitions. Patients were classified as having PC if they had an ICD-10 diagnosis code for PC (Z51.5) and as hospice discharge (HD) if their hospital disposition was ‘hospice’ (home or inpatient). Use proportions for specialties were compared by group and by subgroups with increasing risk of poor outcome.Results There were 16M hospitalizations from 1024 hospitals (9.3% trauma, 26.3% surgical and 64.4% medical) with 53.7% women, 84.5% white and 38.7% >80 years. Overall, 6.2% received PC and 4.1% a HD. Both rates were higher in trauma patients (HD: 3.6%, PC: 6.3%) versus surgical patients (HD: 1.5%, PC: 3.0%), but lower than in medical patients (HD: 5.2%, PC: 7.5%). PC rates increased in higher risk patient subgroups and were highest for inpatient HD.Conclusions In this large study of Medicare patients, HD and PC rates varied significantly among specialties. Trauma patients had higher HD and PC utilization rates than surgical, but lower than medical. The presence of comorbidities, frailty and/or severe traumatic brain injury (in addition to advanced age) may be valuable criteria in selection of trauma patients for hospice and PC services. Further studies are needed to inform the most efficient use of hospice and PC resources, with particular focus on both timing and selection of subgroups most likely to benefit from these valuable yet limited resources.Level of evidence Level III, therapeutic/care management.